A kind of long-lasting anti-corrosion pigment and preparation method thereof

By using raw materials such as concave and concave rock stone, zinc phytate, zirconia, etc., combined with specific proportions and preparation methods, a green and environmentally friendly long-term anti-corrosion pigment was developed, which solved the environmental and health hazards of traditional anti-corrosion pigments, and achieved excellent corrosion resistance and environmental protection.

CN119570300BActive Publication Date: 2025-04-18ANKANG JINMAO BIOENGINEERING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510112889.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-18
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

It is difficult to develop a green and environmentally friendly long-term anti-corrosion pigment, and traditional heavy metal-based anti-corrosion pigment has environmental and health hazards.

Method used

A long-term anti-corrosion pigment is prepared by using raw materials such as concave and concave stone, zinc phytate, zirconia, silane coupling agent, lanthanum ricinoleate and modified Ti3C2Tx nanosheets through specific ratios and preparation methods.

Benefits of technology

This long-term corrosion-resistant pigment has excellent corrosion resistance, and has significantly improved acid resistance, alkali resistance, salt water resistance and salt spray resistance, and is highly environmentally friendly, making it suitable for promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570300B_ABST
    Figure CN119570300B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of anti-corrosion pigments, and in particular to a long-lasting anti-corrosion pigment and a preparation method thereof. The long-lasting anti-corrosion pigment comprises the following raw materials in parts by weight: 40-60 parts of attapulgite, 10-30 parts of zinc phytate, 5-10 parts of zirconium oxide, 1-3 parts of a silane coupling agent, 8-15 parts of lanthanum ricinoleate, and modified Ti 3 C 2 T x The long-lasting anti-corrosion pigment of the present invention comprises lanthanum ricinoleate, modified Ti 3 C 2 T x Nanosheets and other ingredients. Lanthanum ricinoleate, modified Ti 3 C 2 T x Nanosheets can effectively improve the corrosion resistance of pigments. The pigment obtained by the present invention has excellent corrosion resistance. Experimental results show that the acid resistance of the pigment obtained by the present invention is greater than 36 days, the alkali resistance is greater than 32 days, the salt water resistance is greater than 45 days, and the salt spray resistance is greater than 20 days.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion pigments, and in particular to a long-acting anti-corrosion pigment and a preparation method thereof. Background Art

[0002] Anti-corrosion coatings are an effective means of protecting metals and are widely used in various application fields of industrial coatings. As a key component of anti-corrosion coatings, anti-corrosion pigments play a decisive role in the quality of anti-corrosion effects.

[0003] Anticorrosion pigments are divided into toxic anticorrosion pigments and non-toxic anticorrosion pigments, which are further subdivided into lead series, chromium series, molybdate series, phosphate series, phosphomolybdate series, etc. Among them, lead series and chromium series belong to toxic anticorrosion pigments. Although the anticorrosion performance is relatively excellent, the toxicity is very large, causing harm to the environment and human health, and has been banned. And non-toxic anticorrosion pigments, although assisted by physical anticorrosion pigments such as aluminum powder, zinc powder, flaky zinc powder, etc., still have problems such as poor anticorrosion performance and difficulty in achieving long-term corrosion protection. Traditional anticorrosion pigments are mainly heavy metals, but the use of heavy metals will harm the environment and human health. As a result, a variety of new green and environmentally friendly anticorrosion pigments have emerged, such as zinc calcium phosphomolybdate, aluminum-modified zinc phosphate, ultrafine zinc phosphate, zinc phosphomolybdate, silicon-modified zinc phosphate, etc., whose anticorrosion performance has been greatly improved, but still cannot meet the requirements of long-term corrosion protection, and the price is high, which is difficult to promote and apply. Based on this, it is necessary to develop a green and environmentally friendly long-term anticorrosion pigment. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, one of the objects of the present invention is to provide a long-lasting anti-corrosion pigment having excellent corrosion resistance.

[0005] The second object of the present invention is to provide a method for preparing a long-lasting anti-corrosion pigment, which is simple to operate.

[0006] One of the purposes of the present invention is achieved by the following technical solution:

[0007] A long-lasting anti-corrosion pigment comprises the following raw materials by weight: 40-60 parts of attapulgite, 10-30 parts of zinc phytate, 5-10 parts of zirconium oxide, 1-3 parts of silane coupling agent, 8-15 parts of lanthanum ricinoleate, modified Ti3C2T x 5-10 parts of nanosheets.

[0008] Furthermore, the following raw materials are included by weight: 50 parts of attapulgite, 22 parts of zinc phytate, 7 parts of zirconium oxide, 2 parts of silane coupling agent, 12 parts of lanthanum ricinoleate, modified Ti3C2T x 8 parts of nanosheets.

[0009] Furthermore, the modified Ti3C2T x The preparation process of nanosheets is as follows:

[0010] Ti3C2T x The nanosheets, [1,2,4]triazole[1,5,A]pyrimidine-7-amino, isoamyl nitrite and DMF are mixed and heated to react, and the mixture is purified to obtain the product.

[0011] Furthermore, the Ti3C2T x The usage ratio of nanosheets, [1,2,4]triazole[1,5,A]pyrimidine-7-amino, isopentyl nitrite, and DMF is (30-40) mg: (500-600) mg: 1 mL: (40-50) mL.

[0012] Furthermore, the temperature of the heating reaction is 55-65° C., and the time of the heating reaction is 24-30 hours.

[0013] Furthermore, the silane coupling agent is KH550.

[0014] The second object of the present invention is achieved by adopting the following technical solution:

[0015] The preparation method of the above-mentioned long-lasting anti-corrosion pigment comprises the following steps:

[0016] (1) Weighing the raw materials according to the above weight ratio, and preparing slurries of zinc phytate, attapulgite and zirconium oxide respectively;

[0017] (2) adding the zirconium oxide slurry obtained in step (1) to the attapulgite slurry, then adding the zinc phytate slurry, and then adding the silane coupling agent to react, and obtaining the product after filtering, washing, and vacuum drying;

[0018] (3) The product obtained in step (2) is mixed with lanthanum ricinoleate and modified Ti3C2T x The nanosheets are mixed and stirred evenly to obtain a long-lasting anti-corrosion pigment.

[0019] Furthermore, in step (2), the reaction temperature is 60-80° C., and the reaction time is 3-6 h.

[0020] Furthermore, in step (3), the stirring speed is 300-500 rpm, and the stirring time is 3-6 min.

[0021] Furthermore, in step (1), the particle size of the zinc phytate slurry is less than 0.1 μm, the particle size of the attapulgite slurry is less than 5 μm, and the particle size of the zirconium oxide slurry is less than 1 μm.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The long-lasting anti-corrosion pigment of the present invention comprises lanthanum ricinoleate, modified Ti3C2T x Nanosheets. Lanthanum ricinoleate, modified Ti3C2T x Nanosheets can effectively improve the corrosion resistance of pigments. Specifically, lanthanum ricinoleate can not only reduce the surface energy of anti-corrosion pigments, thereby enhancing the compatibility between pigments and coatings, making the coating system more stable; at the same time, lanthanum ions also have strong coordination and complexing effects, and can react with chloride ions in the corrosive environment to form stable compounds, thereby effectively blocking the corrosion of chloride ions on the substrate and significantly improving the corrosion resistance of the coating. x After grafting [1,2,4]triazole[1,5,A]pyrimidine-7-amino on the nanosheets, the Ti3C2T x The surface properties of the nanosheets improve their chemical stability, which helps to reduce the degradation and failure of the coating in a corrosive environment. x The nanosheets retain the Ti3C2T x The original two-dimensional layered structure of the nanosheets can form a "maze effect" in the coating, effectively isolating corrosion factors and increasing the path length for the corrosive medium to reach the surface of the substrate, thereby improving the corrosion resistance of the coating.

[0024] (2) In addition, the long-lasting anti-corrosion pigment of the present invention also contains attapulgite, a silane coupling agent and zinc phytate. Attapulgite has high barrier properties and can coat zirconium oxide and zinc phytate on its surface through the action of the silane coupling agent, thereby improving the dispersion uniformity of the various components in the pigment. At the same time, the binding ability between the phosphate groups in zirconium oxide and zinc phytate and the metal ions together forms a dense passivation protective film, which can effectively prevent the corrosive medium from contacting the metal surface, thereby significantly improving the corrosion resistance effect.

[0025] (3) The experimental results show that the pigment obtained by the present invention has an acid resistance of more than 36 days, an alkali resistance of more than 32 days, a salt water resistance of more than 45 days, and a salt spray resistance of more than 20 days. It can be seen that the pigment obtained by the present invention has excellent corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is modified Ti3C2T x Schematic diagram of the nanosheet preparation process. DETAILED DESCRIPTION

[0027] The present invention will be further described below in conjunction with specific embodiments. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. The specific conditions not specified in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0028] In the embodiment of the present invention, Ti3C2T x The preparation method of the nanosheets is as follows:

[0029] According to the dosage ratio of LiF, Ti3AlC2 powder and hydrochloric acid (1g:0.5g:10mL), Ti3AlC2 powder was added into a mixed solution of LiF and hydrochloric acid with a concentration of 9mol / L. The mixture was stirred at 35℃ for 24h, centrifuged and washed until the pH of the supernatant was neutral. Multilayer Ti3C2T x Nanosheets, multilayer Ti3C2T x The nanosheets were dispersed in deionized water and ultrasonically exfoliated while passing inert gas. x The solution was centrifuged at 3000 rpm for 1.2 h, and the supernatant was collected and freeze-dried to obtain Ti3C2T x Nanosheets.

[0030] The preparation method of lanthanum ricinoleate is as follows: 9 g of lanthanum nitrate hexahydrate, 6 g of ricinoleic acid and 200 mL of ethanol are added to a three-necked flask respectively, and after stirring and dissolving, 100 mL of 8 g / L sodium hydroxide ethanol solution is slowly added dropwise at 70° C. to react for 1 hour, and after washing with deionized water, it is dried in a vacuum oven at 50° C. for 24 hours to obtain lanthanum ricinoleate.

[0031] 1. Implementation

[0032] Example 1

[0033] Example 1 provides a long-lasting anti-corrosion pigment, which is composed of the following raw materials in parts by weight: 50 parts of attapulgite, 22 parts of zinc phytate, 7 parts of zirconium oxide, 2 parts of KH550, 12 parts of lanthanum ricinoleate, and modified Ti3C2T x 8 parts of nanosheets.

[0034] Among them, modified Ti3C2T x The preparation process of nanosheets is as follows:

[0035] According to Ti3C2T x The amount ratio of nanosheets, [1,2,4]triazole [1,5,A] pyrimidine-7-amino, isoamyl nitrite, and DMF was 35 mg: 550 mg: 1 mL: 45 mL.x Nanosheets, [1,2,4]triazole [1,5,A] pyrimidine-7-amino, isoamyl nitrite, and DMF were mixed and reacted at 60°C for 28 hours. After filtering, a solid precipitate was obtained. After washing with DMF and methanol in turn, it was vacuum dried at 50°C for 24 hours to obtain the obtained product. The preparation process is shown in FIG. Figure 1 .

[0036] Example 1 also provides a method for preparing the above-mentioned long-lasting anti-corrosion pigment, which is as follows:

[0037] (1) Weighing the raw materials according to the above weight ratio, and preparing slurries of zinc phytate, attapulgite and zirconium oxide, respectively, wherein the particle size of the zinc phytate slurry is less than 0.1 μm, the particle size of the attapulgite slurry is less than 5 μm, and the particle size of the zirconium oxide slurry is less than 1 μm;

[0038] (2) adding the zirconium oxide slurry obtained in step (1) to the attapulgite slurry, then adding the zinc phytate slurry, and then adding KH550, reacting at 70° C. for 5 h, filtering, washing, and vacuum drying to obtain a product;

[0039] (3) The product obtained in step (2) is mixed with lanthanum ricinoleate and modified Ti3C2T x The nanosheets were mixed and dispersed at 400 rpm for 5 min to obtain a long-lasting anti-corrosion pigment.

[0040] Example 2

[0041] Example 2 provides a long-lasting anti-corrosion pigment, which is composed of the following raw materials in parts by weight: 40 parts of attapulgite, 10 parts of zinc phytate, 5 parts of zirconium oxide, 1 part of KH550, 8 parts of lanthanum ricinoleate, and modified Ti3C2T x 5 parts of nanosheets.

[0042] Among them, modified Ti3C2T x The preparation process of nanosheets is as follows:

[0043] According to Ti3C2T x The amount ratio of nanosheets, [1,2,4]triazole [1,5,A] pyrimidine-7-amino, isoamyl nitrite, and DMF was 30 mg: 500 mg: 1 mL: 40 mL. x Nanosheets, [1,2,4]triazole[1,5,A]pyrimidine-7-amino, isoamyl nitrite and DMF were mixed and reacted at 55°C for 30 hours. After filtering, a solid precipitate was obtained. The solid precipitate was washed with DMF and methanol in sequence and dried in vacuum at 50°C for 24 hours.

[0044] Example 2 also provides a method for preparing the above-mentioned long-lasting anti-corrosion pigment, which is as follows:

[0045] (1) Weighing the raw materials according to the above weight ratio, and preparing slurries of zinc phytate, attapulgite and zirconium oxide, respectively, wherein the particle size of the zinc phytate slurry is less than 0.1 μm, the particle size of the attapulgite slurry is less than 5 μm, and the particle size of the zirconium oxide slurry is less than 1 μm;

[0046] (2) adding the zirconium oxide slurry obtained in step (1) to the attapulgite slurry, then adding the zinc phytate slurry, and then adding KH550, reacting at 60° C. for 6 h, and obtaining the product after filtering, washing, and vacuum drying;

[0047] (3) The product obtained in step (2) is mixed with lanthanum ricinoleate and modified Ti3C2T x The nanosheets were mixed and dispersed at 300 rpm for 6 min to obtain a long-lasting anti-corrosion pigment.

[0048] Example 3

[0049] Example 3 provides a long-lasting anti-corrosion pigment, which is composed of the following raw materials in parts by weight: 60 parts of attapulgite, 30 parts of zinc phytate, 10 parts of zirconium oxide, 3 parts of KH550, 15 parts of lanthanum ricinoleate, and modified Ti3C2T x 10 parts of nanosheets.

[0050] Among them, modified Ti3C2T x The preparation process of nanosheets is as follows:

[0051] According to Ti3C2T x The amount ratio of nanosheets, [1,2,4]triazole [1,5,A] pyrimidine-7-amino, isoamyl nitrite, and DMF was 40 mg: 600 mg: 1 mL: 50 mL. x Nanosheets, [1,2,4]triazole[1,5,A]pyrimidine-7-amino, isoamyl nitrite and DMF were mixed and reacted at 65°C for 24 hours. Solid precipitates were obtained after filtration. The solid precipitates were washed with DMF and methanol in sequence and dried under vacuum at 50°C for 24 hours.

[0052] Example 3 also provides a method for preparing the above-mentioned long-lasting anti-corrosion pigment, which is as follows:

[0053] (1) Weighing the raw materials according to the above weight ratio, and preparing slurries of zinc phytate, attapulgite and zirconium oxide, respectively, wherein the particle size of the zinc phytate slurry is less than 0.1 μm, the particle size of the attapulgite slurry is less than 5 μm, and the particle size of the zirconium oxide slurry is less than 1 μm;

[0054] (2) adding the zirconium oxide slurry obtained in step (1) to the attapulgite slurry, then adding the zinc phytate slurry, and then adding KH550, reacting at 80° C. for 3 h, filtering, washing, and vacuum drying to obtain a product;

[0055] (3) The product obtained in step (2) is mixed with lanthanum ricinoleate and modified Ti3C2T x The nanosheets were mixed and dispersed at 500 rpm for 3 min to obtain a long-lasting anti-corrosion pigment.

[0056] (II) Comparative Example

[0057] Comparative Example 1

[0058] The difference between Comparative Example 1 and Example 1 is that lanthanum oxide is used instead of lanthanum ricinoleate.

[0059] Comparative Example 2

[0060] The difference between Comparative Example 2 and Example 1 is that lanthanum ricinoleate is omitted.

[0061] Comparative Example 3

[0062] The difference between Comparative Example 3 and Example 1 is that Ti3C2T x Nanosheets instead of modified Ti3C2T x Nanosheets.

[0063] Comparative Example 4

[0064] The difference between Comparative Example 4 and Example 1 is that Ti3C2T x Nanosheets and [1,2,4]triazole[1,5,a]pyrimidine-7-amino instead of modified Ti3C2T x Nanosheets, Ti3C2T x The amounts of nanosheets and [1,2,4]triazole[1,5,A]pyrimidine-7-amino used were the same as those in Example 1.

[0065] (III) Experimental examples

[0066] Experimental Example 1

[0067] The pigments obtained in Examples 1-3 and Comparative Examples 1-4 were added to a water-based iron oxide red epoxy system, and the corrosion resistance was tested as follows:

[0068] The water-based epoxy iron red system is composed of the water-based epoxy iron red primer, which is 350g of STW602 water-based epoxy emulsion, 40g of the above-mentioned pigments, and 30g of zinc phosphate.

[0069] Acid resistance: Tested according to the method in standard GB / T 1763-1979 (1989), observing the bubbling time, the results are shown in Table 1;

[0070] Alkali resistance: Tested according to the method in GB / T 1763-1979 (1989), observing the bubbling time, the results are shown in Table 1;

[0071] Salt water resistance: Tested according to the method in GB / T 1763-1979 (1989), observing the bubbling time, the results are shown in Table 1;

[0072] Salt spray resistance: Tested according to the method in standard GB / T 1771-2007, and the blistering time was observed. The results are shown in Table 1.

[0073] Table 1

[0074]

[0075] It can be seen from Table 1 that the pigments obtained in Examples 1-3 have excellent corrosion resistance.

[0076] Compared with Examples 1-3, Comparative Example 1 uses lanthanum oxide instead of lanthanum ricinoleate, and Comparative Example 2 omits lanthanum ricinoleate, and the corrosion resistance of the obtained pigment is reduced. Further analysis shows that the addition of lanthanum ricinoleate can not only reduce the surface energy of the anti-corrosion pigment, but also enhance the compatibility between the pigment and the coating, making the coating system more stable; at the same time, lanthanum ions also have a strong coordination and complexing effect, and can react with chloride ions in the corrosive environment to form a stable compound, thereby effectively blocking the corrosion of chloride ions on the substrate and significantly improving the corrosion resistance of the coating.

[0077] Compared with Examples 1-3, Comparative Example 3 uses Ti3C2T x Nanosheets instead of modified Ti3C2T x Nanosheets, Comparative Example 4 uses Ti3C2T x Nanosheets and [1,2,4]triazole[1,5,a]pyrimidine-7-amino instead of modified Ti3C2T x Nanosheets, the corrosion resistance of the obtained pigment is reduced. Further analysis shows that in Ti3C2T x After grafting [1,2,4]triazole[1,5,A]pyrimidine-7-amino on the nanosheets, the Ti3C2T x The surface properties of the nanosheets improve their chemical stability, which helps to reduce the degradation and failure of the coating in a corrosive environment. x The nanosheets retain the Ti3C2T x The original two-dimensional layered structure of the nanosheets can form a "maze effect" in the coating, effectively isolating corrosion factors and increasing the path length for the corrosive medium to reach the surface of the substrate, thereby improving the corrosion resistance of the coating.

[0078] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A long-lasting anti-corrosion pigment, characterized in that: The raw materials include the following by weight: 40-60 parts of attapulgite, 10-30 parts of zinc phytate, 5-10 parts of zirconium oxide, 1-3 parts of silane coupling agent, 8-15 parts of lanthanum ricinoleate, modified Ti3C2T x 5-10 parts of nanosheets; The modified Ti3C2T x The preparation process of nanosheets is as follows: Ti3C2T x The nanosheets, [1,2,4]triazole[1,5,A]pyrimidine-7-amino, isoamyl nitrite and DMF are mixed and heated to react, and then purified to obtain the product.

2. The long-lasting anti-corrosion pigment according to claim 1, characterized in that: The raw materials include the following by weight: 50 parts of attapulgite, 22 parts of zinc phytate, 7 parts of zirconium oxide, 2 parts of silane coupling agent, 12 parts of lanthanum ricinoleate, modified Ti3C2T x 8 parts of nanosheets.

3. The long-lasting anti-corrosion pigment according to claim 1, characterized in that: The Ti3C2T x The usage ratio of nanosheets, [1,2,4]triazole[1,5,A]pyrimidine-7-amino, isopentyl nitrite, and DMF is (30-40) mg: (500-600) mg: 1 mL: (40-50) mL.

4. The long-lasting anti-corrosion pigment according to claim 1, characterized in that: The temperature of the heating reaction is 55-65° C., and the time of the heating reaction is 24-30 hours.

5. The long-lasting anti-corrosion pigment according to claim 1 or 2, characterized in that: The silane coupling agent is KH550.

6. The method for preparing the long-lasting anti-corrosion pigment according to claim 1 or 2, characterized in that: The following steps are involved: (1) Weighing the raw materials according to the weight proportions, and preparing slurries of zinc phytate, attapulgite, and zirconium oxide respectively; (2) adding the zirconium oxide slurry obtained in step (1) to the attapulgite slurry, then adding the zinc phytate slurry, and then adding the silane coupling agent to react, and obtaining the product after filtering, washing, and vacuum drying; (3) The product obtained in step (2) is mixed with lanthanum ricinoleate and modified Ti3C2T x The nanosheets are mixed and stirred to obtain a long-lasting anti-corrosion pigment.

7. The method for preparing the long-lasting anti-corrosion pigment according to claim 6, characterized in that: The reaction temperature in step (2) is 60-80°C, and the reaction time is 3-6h.

8. The method for preparing the long-lasting anti-corrosion pigment according to claim 6, characterized in that: The stirring speed in step (3) is 300-500 rpm, and the stirring time is 3-6 min.

Citation Information

Patent Citations

  • Coating for automobile chassis for off-road vehicle

    CN114539902A

  • Anticorrosive paint applied to petroleum pipeline and preparation method of anticorrosive paint

    CN115368806A